2014
DOI: 10.1177/2167702614529111
|View full text |Cite
|
Sign up to set email alerts
|

Looking on the Dark Side

Abstract: To understand cognitive bases of self-reported ruminative tendencies, we examined interpretations and subsequent memories of ambiguous situations depicting opportunities for rumination. In Experiment 1, we recruited students, randomly assigned them to a distracting or ruminative concentration task, and then measured their latencies to complete fragments that resolved situational ambiguity in either a ruminative or a benign direction. Students in the ruminative task condition who previously self-identified as b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
14
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 47 publications
(14 citation statements)
references
References 50 publications
0
14
0
Order By: Relevance
“…Second, according to the daily experience, the anger-related cognition and emotion that has triggered angry rumination may make it easier for an individual to regard the ambiguous cue or unintentional provocation as hostile or intentional; similarly, the angry rumination may facilitate the development of hostile attribution bias in daily life. For example, a recent study found that a component of rumination leads to a negatively biased direction in interpreting ambiguous cues [18]. Thus, another aim of this study is exploring the longitudinal effect of angry rumination on hostile attribution bias at the same time.…”
Section: Introductionmentioning
confidence: 99%
“…Second, according to the daily experience, the anger-related cognition and emotion that has triggered angry rumination may make it easier for an individual to regard the ambiguous cue or unintentional provocation as hostile or intentional; similarly, the angry rumination may facilitate the development of hostile attribution bias in daily life. For example, a recent study found that a component of rumination leads to a negatively biased direction in interpreting ambiguous cues [18]. Thus, another aim of this study is exploring the longitudinal effect of angry rumination on hostile attribution bias at the same time.…”
Section: Introductionmentioning
confidence: 99%
“…We aim to replicate the evidence for rumination and self-esteem as possible mechanisms of change. In addition, we examine memory bias as potential mediator which is related to rumination [42,43] and self-esteem [44]. Negative bias in recall of self-related information has been recognized as important factor in the development and maintenance of depression (see cognitive model by Beck) [45][46][47][48][49].…”
Section: Introductionmentioning
confidence: 99%
“…A few CBM experiments have modified interpretation biases in ways that affect subsequent measures of memory (e.g., Hertel et al 2014; Joormann et al 2015; Tran et al 2011). However, more direct attempts to modify memory are rare (see Fox et al 2014).…”
Section: Introductionmentioning
confidence: 99%